Muscarinic Receptor: From Structure to Animal Models - Myslivecek, Jaromir; Jakubik, Jan (Neuromethods, 2016)
This volume provides methods for characterization of muscarinic receptor in crystallography studies that advanced our understanding of structural properties and activation mechanism of muscarinic receptors and are cornerstone in molecular modeling and computer‑based approaches to study muscarinic receptors. Muscarinic Receptor: From Structure to Animal Models guides readers through binding techniques, protocols to investigate molecular properties of muscarinic receptors, protocols to study muscarinic receptors in the central nervous system using autoradiography and PET studies, and protocols on animals with knock-out and knock-in muscarinic genes to study role of muscarinic receptors in physiology and behavior. Written in the popular Neuromethods series style, chapters include the kind of detail and key advice from the specialists needed to get successful results in your own laboratory.  Concise and easy-to-use, Muscarinic Receptor: From Structure to Animal Models aims to ensure successful results in the further study of this vital field